Reconsidering The Concept Of The Greater Middle East: Patterns Of Regional And Subregional Development Dynamic - Mnatsakanyan, Vilen (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The Greater Middle East region is one of the main trend makers both in the context of geopolitical processes and in terms of geo-economic and regional shifts in the global economic situation. Rapid economic growth and high involvement in major geopolitical processes make the study of the regional aspect of this issue extremely relevant. The author analyzes the economic, demographic, and logistical aspects of the formation of this region and its current state, as well as the perception of a group of these countries as a separate region by both external players and internal actors. The author concludes that by all the identified criteria, the region is extremely heterogeneous; therefore, both in terms of academic study and in the issue of foreign policy formation, more attention should be paid to sub-regional processes and transformations, which can lead to the development of more effective approaches to understanding the ways of productive communication with the countries of the region
Keywords: Demographics